PENETAPAN KADAR SENYAWA FENOLIK EKSTRAK ETANOL 70% DAUN PUCUK MERAH (Syzygium myrtifolium Walp.) DENGAN METODE FOLIN-CIOCALTEU - Dewi Nofita; Delviona Friti Rahman (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2025)
Abstract: Syzygium myrtifolium Walp. (pucuk merah) is a decorative species often found in urban settings, including sidewalks and gardens. The vibrant red foliage of this plant is rich in bioactive compounds, such as phenolics, flavonoids, alkaloids, triterpenoids, and steroids, which serve as natural antioxidants. This research aims to determine the concentration of phenolic compounds in a 70% ethanol extract of red shoot leaves, using gallic acid as a reference standard. The analysis revealed that the optimal wavelength for gallic acid was 770 nm, with a linear regression equation of ŷ = 0.1211 + 0.0087x. A coefficient of determination (R²) of 0.9969 and a correlation coefficient (r) of 0.9984 were achieved. The total phenolic content in the 70% ethanol extract of red shoot leaves was found to be 858.9 ± 0.0076 mg GAE/g of extract.